Family and non-family business differences in Estonia - Kirsipuu, Maret (Estonian Discussions on Economic Policy, 2014)
This paper seeks to identify differences between family enterprises and non-family enterprises. The concepts of entrepreneurship, entrepreneur and enterprise/business are clarified. The paper contains the results of research conducted by the author among family entrepreneurs in 2007–2012 that can be compared to the research results reached by Wahl (2011). This research demonstrates that there are differences between family entrepreneurs and non-family entrepreneurs, which are primarily caused by that family entrepreneurs value first of all their family members, family traditions and only then profit earning.